Major oxide geochemistry of Okeigbo stream sediments in Akungba-Akoko, southwestern Nigeria: implications for chemical classification and provenance - O. Obaje, Solomon; Tejuoso, O. S. (International Journal of Advanced Geosciences, 2024)
In this paper, major oxide concentrations in Okeigbo stream sediments were used to chemically classify them and to determine their provenance. The study area lies in Akungba-Akoko area of Ondo State, southwestern Nigeria. Seventeen samples were collected and analyzed using Energy Dispersive X-ray Fluorescence Spectrometer. The major oxides analyzed in the samples are SiO2, Al2O3, Fe2O3, TiO2, K2O, CaO, MnO and P2O5. The average concentration values of SiO2, Al2O3 and Fe2O3 are 56.50 wt. %, 13.50 wt. % and 10.70 wt. %, respectively. On the other hand, the average concentration values of K2O and CaO are 6.30 wt. % and 4.99 wt. %, respectively, while TiO2, MnO and P2O5 have values < 1.00 wt. %. Okeigbo stream sediments are classified using the plot of log10(SiO2/Al2O3) versus log10(Fe2O3/K2O) to be 89.0% greywackes, 10.0% litharenites and 10.0% arkose. The average value of 4.28 for SiO2/Al2O3 indicates that the sediments originated from majorly acid igneous source rock, while the average value of 1.73 for Fe2O3/K2O is indicative of mineralogically stable sediments.